Analysis of Digital Transformation and Digital Leadership in Improving Employee Performance at Sekolah Tinggi Ilmu Ekonomi (STIE) APRIN Palembang - Indriani, Indriani (Jurnal Ar Ro'is Mandalika (Armada), 2024)
This study employs a quantitative approach to analyze the influence of Digital Transformation and Digital Leadership on Employee Performance at STIE APRIN. The research population consists of 40 employees; due to the relatively small size, a saturated sampling technique was used, meaning the entire population was included as the research sample. The research instrument was a structured questionnaire developed based on theoretical indicators of each variable. Prior to analysis, the instrument’s quality was evaluated through validity testing (using Pearson correlation) and reliability testing using Cronbach’s Alpha, where items were considered valid if r calculated > r table and reliable if α ≥ 0.60. Data normality was tested using the Kolmogorov–Smirnov test to ensure a normal distribution, and multicollinearity was assessed via Tolerance and Variance Inflation Factor (VIF) values (with thresholds: Tolerance > 0.10 and VIF < 10) to ensure no strong intercorrelation among independent variables. Relationships among variables were analyzed using multiple linear regression analysis. The model’s explanatory power was measured through the coefficient of determination (R²), while the F-test was applied to examine the simultaneous effect of independent variables on the dependent variable. To determine the individual influence of each independent variable, partial t-tests were conducted. All data analyses were performed using SPSS version 24, with a significance level set at 5%. This methodological approach ensures that the research instrument is both valid and reliable, that classical assumptions are met, and that the statistical tests provide credible empirical evidence regarding the extent to which Digital Transformation and Digital Leadership impact employee performance.